Asymptotic Analysis of a Wnt/β-catenin pathway model - Μαρής, Δημήτριος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών, 2014)
The Wnt/β catenin signaling pathway introduced by Lee et al. in 2003 is analyzed with the Computational Singular Perturbation method (CSP).